Avaliação do uso de resíduo de vidro na produção de pisos polidos - Guimarães, Goubyan Borges (2013)
Conventionally the floors mortar are composed of ground mineral aggregates that mixed with Portland cement have extensive use in large enterprises. In this work was evaluated the possibility to aplicate glass waste to replace the mineral aggregates used in the manufacture of polished floors. Samples were produced with natural aggregate, used as reference, and plates with glass waste with two types of cement. The objective was to determine the physical and mechanical performance of the offered material, allied with the recycling of glass residue. Tests were conducted of water absorption, deep abrasion and bending test. Accelerated test of alkali aggregate reaction was realized on the samples to assess the possibility of alkali-silica reaction. Posteriorly, we realized analyse scanning electron microscopy and X ray diffraction. At the end there was not loss in properties in terms of water absorption and deep abrasion, in the samples produced with glass residue in relation to the samples produced with natural aggregate. There was only reduction in the flexural strength in the results obtained at 180 days of age. Among the samples produced with glass waste, was found high possibility of occurrence of the Alkali Silica Reaction in the samples produced with CPII F40, that occurred less expressive may, in the samples produced with CPIV 32.